Tube-cantilever double resonance enhanced fiber-optic photoacoustic spectrometer. (March 2020) - Chen, Ke; Deng, Hong; Guo, Min; Luo, Chen; Liu, Shuai; Zhang, Bo; Ma, Fengxiang; Zhu, Feng; Gong, Zhenfeng; Peng, Wei; Yu, Qingxu
Highlights: The tube-cantilever double resonance enhanced fiber-optic PAS was proposed. The first-order resonant frequencies of the PA tube and the cantilever were equal. The detection limit (1σ) for trace acetylene detection was achieved to be 27 ppt. The NNEA coefficient reached 4.2 × 10 −10  cm −1  W Hz −1/2 . Abstract: An ultra-high sensitive trace gas detection method based on tube-cantilever double resonance enhanced fiber-optic photoacoustic spectroscopy (PAS) is proposed. The first-order resonant frequencies of the acoustic resonant tube and the fiber-optic cantilever microphone were both equal to the frequency of the photoacoustic pressure signal. This method combines the amplitude amplification of the photoacoustic pressure wave in an acoustic resonant tube with the response enhancement of the photoacoustic signal by the cantilever, making the gas detection extremely sensitive. An experimental double resonance enhanced photoacoustic spectrometer was built for trace acetylene detection at the wavelength of 1532.83 nm. A noise equivalent detection limit (1 σ ) was achieved to be 27 ppt with a 200-s averaging time, which is the best value reported so far. In addition, the normalized noise equivalent absorption (NNEA) coefficient reached 4.2 × 10 −10  cm −1  W Hz −1/2 .